(untitled) (Iraqi Journal of Medical Sciences, 2021)
Background: The blood of blood donors is screening for hepatitis B virus (HBV), hepatitis C virus (HCV), and human immunodeficiency virus (HIV) infection by enzyme immunoassay (EIA) in the National Center of Blood Bank in Baghdad. The residual risk of EIA negative samples is not estimated till now in Iraq. Objective: To detect HBV, HCV and HIV viruses within seronegative plasma of blood donors by a commercially available multiplex nucleic acid amplification tests (NAT) with mini-pooling system. Methods: One thousand (1000) blood donors were screened by EIA revealed negative results then NAT was performed on pools of samples, each pool contain ten seronegative plasmas (MP10) i.e., 100 minipools. Results: The detected positive minipools 10 seronegative plasmas by NAT for HBV, HCV and HIV were 3 MP10. Conclusion: The use of NAT appeared to be sensitive and reliable to detect occult HBV and overcome the seroconversion problem related with HCV and HIV within seronegative plasmas of blood donors. Therefore, the implementation of NAT with mini-pooling in addition to serological tests for routine blood donor screening will improve and ensure the safety of blood transfusion in Iraq. Keywords: Blood transfusion, widow period, multiplexes PCR Citation: Majid GS, Abdulamir AS, Ahmed AM, Aufi IM, Abdullah OI. The using of multiplex RT-qPCR for pooled samples to detect hepatitis B virus, hepatitis C virus, human immunodeficiency virus within Iraqi blood donors. Iraqi JMS. 2021; 19(1): 99-106. doi: 10.22578/IJMS.19.1.13